The Liberated Tongue of Elaine Vilar Madruga: Heroism, Sexuality and Gender in "La tiranía de las moscas" (2021) - Asencio Serrano, Cristina (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
This article explores contemporary Cuban narrative written by women, focusing on the figure of Elaine Vilar Madruga, a prominent representative of the new Generation 0.1. Through an analysis of her novel La tiranía de las moscas (2021), we examine the categories of heroism, sexuality, and gender —three constants that permeate Cuban literature of the revolutionary period. In this case, the author constructs new ways of thinking to challenge power and the established system through an innovative and critical perspective that enriches the current literary landscape.
Keywords: Cuban narrative; Elaine Vilar Madruga; Generación 0.1.; heroism; sexuality; gender